Hubungan Pengetahuan Ibu Hamil tentang Buku KIA (Kesehatan Ibu dan Anak) dengan Kunjungan K6 pada Ibu Hamil - Arroyani Lu'luil Ula Al Salsabila; Siti Alfiah; Fitria Nurwulansari (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
ANC visits have not yet become a top priority for some pregnant women. The lack of knowledge about the use of the KIA book, which is still considered only as a health record book for health workers. This study aims to determine the relationship between pregnant mothers' knowledge of the KIA book and K6 visits for pregnant mothers. This research is a type of descriptive-analytical study with a cross-sectional research design. The sample was taken using purposive sampling technique, totaling 104 people. The independent variable in this study is the knowledge of pregnant women about the KIA book, while thedependent variable is the K6 visits for pregnant women. Data collection instruments use questionnaires and data collection sheets. The data analysis used is univariate and bivariate using chi-square. The research results show that the majority have good knowledge and most conduct K6 visits. The results of the chi-square test indicate a relationship between pregnant women's knowledge of the KIA book and K6 visits among pregnant women with a p-value of 0.000. Based on the above description, it can be concluded that there is a significant relationship between pregnant women's knowledge of the KIA book and K6 visits among pregnant women.